1944
DOI: 10.1104/pp.19.2.377
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Roots and Tops of Dioecious Lychnis in Vegetative and Flowering Phases of Growth

Abstract: In viewv of the currenit interest in problemiis of nutritional ontogeniy ancd the evident influeniee of reproductive processes thereon, experimental data on the composition of the dioeeious species, Lychlnis dioica L., are presented. Dioecious forms appear to have the advantage in studies of this type in permitting recogniitioni of coimipositionial and metabolic differenlees associated with sex expression. Bv virtue of their perennial habit, individual plants of Lychnis can be studied througohout their growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1955
1955
1999
1999

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
(3 reference statements)
1
5
0
Order By: Relevance
“…In this study, however, neither biomass (size) nor N pools were dierent between sexes. The larger P pools of male plants in this study were previously also found by Stan®eld (1944), indicating that males have larger and/ or more ecient root systems compared to females.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In this study, however, neither biomass (size) nor N pools were dierent between sexes. The larger P pools of male plants in this study were previously also found by Stan®eld (1944), indicating that males have larger and/ or more ecient root systems compared to females.…”
Section: Discussionsupporting
confidence: 68%
“…In other studies of S. dioica, females showed higher metabolic rates (Stan®eld 1944), higher survival after defoliation (Elmqvist and Gardfjell 1988), and were larger compared to males (Nigtevecht 1966). In this study, however, neither biomass (size) nor N pools were dierent between sexes.…”
Section: Discussionmentioning
confidence: 94%
“…Such a seasonal pattern in the concentrations of N and P in aboveground shoots has previously been documented in other populations of R. chamaemorus (Saeb0 1968, 1970, Taylor and Marks 1971, Chapin et al 1980, as well as in other deciduous species (e.g., Chapin et al 1980, Whigham 1984, Abrahamson and McCrea 1985. The concentrations of nutrients have been reported to differ between male and female plants of Cannabis sativa, Spinacea oleracea, Silene dioica, and a few other species (Loehwing 1933, Stanfield 1937, 1944, Kotaeva and Chkhubianishvili 1978. In R. chamaemorus, differences in nutrient concentrations between sexes do not appear to be consistent between populations.…”
Section: Nutrient Concentrationsmentioning
confidence: 62%
“…These data need to be interpreted with caution both because they concern a phylogenetically limited set of plant species, and because repeated measurements in some species have shown that sexual differences in nutrient concentrations may not be expressed in all populations, nor throughout the whole growing season (e.g., Agren 1987Agren , 1988a. There are very few comparisons of concentrations of nutrients other than nitrogen in male and female plants (for examples see Loehwing 1933;Stanfield 1944; Table 1). …”
Section: Correlates Of Sexual Differences In Herbivore Damagementioning
confidence: 97%